Effect of fructooligosaccharides on the colonization of Lactobacillus rhamnosus AS 1.2466T in the gut of mice - Zhihua Niu; Meijuan Zou; Tingting Bei; Na Zhang; Dongyao Li; Miaoshu Wang; Chen Li; Hongtao Tian (Food Science and Human Wellness, 2023)
Lactobacillus rhamnosus and fructooligosaccharides (FOS) have been widely studied so far. However, the effects of L. rhamnosus on the intestinal microecological environment at the species level and the effect of different proportions of FOS on L. rhamnosus colonization in different parts of mice intestine are still unclear. The study results indicated that the specific bands of enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) in the L. rhamnosus (LR) group significantly increased at 7 days. Although the number of bands was similar to the natural recovery (NR) group, the brightness of few bands significantly enhanced in the later stage of recovery. Besides, Southern-blot maps showed strong signals, indicating that the ERIC-PCR fingerprint could accurately reflect the changes in the mouse gut microbiota diversity. Further, the high-throughput results confirmed that the Lactobacillus and Akkermansia had different changes at different periods, but all of them showed an upward trend, while the Klebsiella were inhibited, thereby maintaining the intestinal microecology balance. Moreover, FOS exerted a positive effect on L. rhamnosus colonization in the gut.